Taking a Stand: The Genetics Community's Responsibility for Intelligence Research - Callier, Shawneequa L. (The Hastings Center report, 2015)
There is a longstanding debate about genetics research into intelligence. Some scholars question the value of focusing on genetic contributions to intelligence in a society where social and environmental determinants powerfully influence cognitive ability and educational outcomes. Others warn that censoring certain research questions, such as inquiries about genetic differences in intellectual potential, compromises academic freedom. Still others view interest in this subject as a corollary to a long and troublesome history of eugenics research. The dawn of a new era in genome sequencing as a commodity will sustain scientific interest in the genetics of intelligence for the foreseeable future, but deep-rooted challenges threaten the scientific merit of the research. The use of imprecise definitions of study populations, the difficult nature of studying the environment, and the potential of researcher bias are inextricably linked with concerns about the trustworthiness and utility of research in this area. Leadership by the genetics community is essential to ensure the value and trustworthiness of these studies.